Rich Design Research Space - Sevaldson, Birger (FormAkademisk, 2008)
This paper introduces and discusses a Rich Research Space as an inclusive methodological framework and scaffold for research-by-design. The Rich Research Space especially addresses the issue of richness in design processes and design-led research. There is a general trend towards increased complexity in design processes, caused on one hand by the increasing depth and width in the use of design media and methods, and on the other hand by the increasing complexity and interdependency of society due to globalisation. These issues confront the designer-researcher with new challenges. This paper formulates a research strategy for research-by-design in fields that have a high degree of richness in the use of media, the amount of information, and the methods involved. The Rich Research Space concept proposed takes into account the physical, social, and cultural spaces, and the virtual and visual media spaces in which the research-by-design takes place. The concept takes the form of a specific integral approach to design, and a holistic theoretical mindset. It embraces many types of investigation, from analytical to intuitive. The Rich Research Space provides a flexible framework within which the complexity of research-by-design can be interrelated, discussed, and reflected upon. Potentially, it can create a more involved role for the designer-researcher, a role that allows contributions towards the resolution of ever more pressing issues in our society. This approach is currently one of a limited number of possible frameworks that the design professions can utilize in order to make a difference in a world of at times overwhelming complexity. The concept of the Rich Research Space is discussed with reference to an art installation called Barely. Keywords: Research by design, collaborative design, complexity, creativity, research methods.